Impact of networking, entrepreneurial capability, market access and government initiatives on Johor start-up SME's performance / Hamizah Zaharudin and Gelbino Morris - Zaharudin, Hamizah; Morris, Gelbino (2021)
Small Medium Enterprise (SMEs) are continuously facing challenges, be it from internal or external factor. However, SMEs have long been recognized as one of the backbones for Malaysia economy. They are the key stimulator for economic growth, build jobs opportunity and lead to the creation of a private sector. However, resulting from Malaysia government enforcement of Movement Control Order (MCO) due to pandemic COVID-19, SMEs was one of the affected groups. As a consequence, most of the SMEs face declining performance in term of their sales, income and revenues. This happens to all SMEs in Malaysia especially start-up SMEs which currently vulnerable in the harsh market environment. This study aims to find out the factors that contribute to start-up SMEs performance in Johor. The factors adopted in this study were studied and suggested by Ghani & Darawi (2012) which use entrepreneurial knowledge and capability, networking, government initiatives and the researcher additionally include market access as independent variables that will influence startup SMEs performance in Johor. The population of the study is 63 successful TUBE programme participants that have register their business under SME Corp Johor in 2019 and 2020. This study has utilized SWOT analysis tools to analyse the current situational analysis of the population and provide some strategies for improving start-up SMEs performance using TOWS analysis. Multiple linear regression analysis result reveal that this research model is moderately good fit to predict the start-up SMEs performance even though all four of the independent variables used in this study does not have a bigger impact on start-up SMEs performance in Johor, this might be cause by the possibility of other higher impact factors exists and contribute to start-up SMEs performance in Johor. However, all of the independent variables prove to have positive relationship to the start-up SMEs performance and comparison between all the independent variables used, entrepreneurial knowledge and capability have a higher impact followed by market access factors, government initiatives factors and networking in business factors. This study will provide various idea on how to improve start-up SMEs performance by widening SMEs owner's knowledge on importance of networking, entrepreneurial knowledge and capability, market access and government initiatives for their business success. By knowing all of these factors, the SMEs owners could prepare for the awaiting challenge as entrepreneur and remain competitive in the future.